Calcium—Nutrient and Messenger - Thor, Kathrin (Frontiers in Plant Science, 2019)
Calcium is an essential element needed for growth and development of plants under both non-stressed and stress conditions. It thereby fulfills a dual function, being not only an important factor for cell wall and membrane stability, but also serving as a second messenger in many developmental and physiological processes, including the response of plants to biotic stress. The perception of non-self hereby induces an influx of calcium ions (Ca2+) into the cytosol, which is decoded into downstream responses ultimately leading to defense. Maintaining intracellular Ca2+ homeostasis is crucial for the ability to generate this signal. This review will describe the current knowledge of the mechanisms involved in uptake and transport of calcium as well as cellular homeostasis and signal generation, describing known genes involved and discussing possible implications the plant’s nutritional status with regard to calcium might have on immunity.